Optimizing therapeutic outcomes: preconditioning strategies for MSC-derived extracellular vesicles - Song, Yuqi; Liang, Fengrui; Tian, Weikun; Rayhill, Erin; Ye, Liping; Tian, Xinghan (Frontiers in Pharmacology, 2025)
Mesenchymal stem cells (MSCs) and MSC-derived extracellular vesicles (MSC-EVs) are increasingly recognized for their therapeutic potential in regenerative medicine, driven by their capabilities in immunomodulation and tissue repair. However, MSCs present risks such as immunogenic responses, malignant transformation, and the potential to transmit infectious pathogens due to their intrinsic proliferative and differentiative abilities. In contrast, MSC-EVs, particularly exosomes (MSC-exosomes, 30–150 nm in diameter), offer a safer therapeutic profile. These acellular vesicles mitigate risks associated with immune rejection and tumorigenesis and are inherently incapable of forming ectopic tissues, thereby enhancing their clinical safety and applicability. This review highlights the therapeutic promise of MSC-exosomes especially focusing on the modulation of miRNA (one of bioactive molecules in MSC-EVs) profiles through various preconditioning strategies such as exposure to hypoxia, chemotherapeutic agents, inflammatory cytokines, and physical stimuli. Such conditioning is shown to optimize their therapeutic potential. Key miRNAs including miR-21, miR-146, miR-125a, miR-126, and miR-181a are particularly noted for their roles in facilitating tissue repair and modulating inflammatory responses. These functionalities position MSC-exosomes as a valuable tool in personalized medicine, particularly in the case of exosome-based interventions. Despite the potential of MSC-EVs, this review also acknowledged the limitations of traditional MSC therapies and advocates for a strategic pivot towards exosome-based modalities to enhance therapeutic outcomes. By discussing recent advances in detail and identifying remaining pitfalls, this review aims to guide future directions in improving the efficacy of MSC-exosome-based therapeutics. Additionally, miRNA variability in MSC-EVs presents challenges due to the diverse roles of miRNAs play in regulating gene expression and cell behavior. The miRNA content of MSC-EVs can be influenced by preconditioning strategies and differences in isolation and purification methods, which may alter the expression profiles of specific miRNAs, contributing to differences in their therapeutic effects.